How Do National Cultures Affect Quality of Life in Europe During the COVID-19 Pandemic? - Somjintana Koompai; Joí«l Royer (Emerging Science Journal, 2022)
Objectives: This study aimed to explore the six cultural dimensions of Geert Hofstede that affect perceptions of quality of life in 26 European countries during the COVID-19 pandemic (April 2020–March 2021): (1) Quality of life, (2) Democracy and trust, (3) Working during COVID-19, (4) Financial situation, (5) Support during COVID-19, and (6) Health care during COVID-19. Many studies are not conclusive on which dimensions of national culture affect the spread and death rate of COVID-19. The researchers, therefore, consider that studying the pandemic from the perception of quality can prevent its spread and contribute to the care and security of people affected by COVID-19. This study may be another way of providing information to those stakeholders. Method: To determine which aspects of culture affect the quality of life of Europeans during the COVID-19 pandemic, the researchers analyzed data through stepwise multiple regression analysis to predict the relationship between independent variables (cultural dimensions) and dependent variables (perceptions of the quality of life). Findings: It was found that during the COVID-19 pandemic, countries with higher power distance and higher uncertainty avoidance had a lower quality of life in several dimensions, mainly in Eastern European countries and Latin European countries (France, Italy, Portugal, and Spain). In the Nordic or Scandinavian countries with higher levels of indulgence, people were more satisfied with their quality of life in spite of the COVID-19 epidemic. Novelty/Improvement:The results may inform policy-makers and stakeholders on how national cultures have both positive (i.e., indulgent and long-term) and negative (high power distance and high uncertainty avoidance) effects on the quality of life of Europeans during the COVID-19 pandemic. There should be (1) short-term measures to provide equal economic measures and public health assistance to reduce anxiety (reduce high power distance and high uncertainty avoidance), (2) medium-term measures to promote education and training to prepare people for new modes of working in the future (decrease high uncertainty avoidance), and (3) long-term measures to cultivate cultures to save for the future and to be optimistic and happy, both mentally and physically (increase long term orientation and indulgence). Doi: 10.28991/esj-2022-SPER-02 Full Text: PDF